Evaluasi Perda Nomor 14 Tahun 2009 terhadap Kebersihan Lingkungan di Kota Tanjung Pinang - Ibrahim Ibrahim; Adi Firmansyah; Syaril Ramadhan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
Environmental cleanliness is a problem that is difficult to control by the local government of Tanjung Pinang City. Environmental cleanliness is an inseparable thing from human life and is a fundamental element in health science and prevention. In this case, the local government of Tanjungpinang City plays an important role in making policies related to the waste problem. When the terms policy and public are combined into one, that is, public policy, it has a broader meaning than when it is interpreted singly. The method in this paper uses a qualitative method, which is a research method used to examine the condition of natural objects, where the researcher is a key instrument, data collection techniques are carried out by triangulation, data analysis is inductive, and the results of the study emphasize the meaning of generalizations. Policy evaluation is generally carried out after the public policy is implemented, in order to see between the level of achievement and failure